2019
DOI: 10.1002/cctc.201900507
|View full text |Cite
|
Sign up to set email alerts
|

High‐Capacity and Long‐Cycle Lifetime Li−CO2/O2 Battery Based on Dandelion‐like NiCo2O4 Hollow Microspheres

Abstract: As a promising energy storage technology, Li−CO2/O2 battery with ultrahigh discharge capacities have received much attention, reaching capacities three times that of Li−O2 batteries. Herein, using an excellent catalyst, NiCo2O4 designed as a 3D dandelion‐like hollow nanostructure, a Li−CO2/O2 battery is systematically investigated to understand how the reaction mechanisms are affected by CO2. With CO2 stabilization, the batteries could achieve a specific discharge capacity as high as 22000 mAh/g and a long‐ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 31 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…A good example is the decoration of TiO 2 nanowires with RuO 2 nanoparticles. [69] The third type is bimetal oxide, [70] such as NiCo 2 O 4 , [71] CoSnO 3 [72] and ZnCo 2 O 4 . [73] The selection of catalysts for LiÀ CO 2 batteries can be guided by the air electrode catalysts of Li-O 2 batteries sometimes.…”
Section: Transition Metals and Their Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…A good example is the decoration of TiO 2 nanowires with RuO 2 nanoparticles. [69] The third type is bimetal oxide, [70] such as NiCo 2 O 4 , [71] CoSnO 3 [72] and ZnCo 2 O 4 . [73] The selection of catalysts for LiÀ CO 2 batteries can be guided by the air electrode catalysts of Li-O 2 batteries sometimes.…”
Section: Transition Metals and Their Compoundsmentioning
confidence: 99%
“…[73] The selection of catalysts for LiÀ CO 2 batteries can be guided by the air electrode catalysts of Li-O 2 batteries sometimes. [71] TMCs, such as VN, [74] RuP 2 , [75] Mo 2 C, [76][77] MoS 2 , [78][79][80] In 2 S 3 [81] and ZnS, [82] with diverse composition and structure variation have been designed and utilized as highly efficient catalysts for LiÀ CO 2 batteries. For example, LiÀ CO 2 battery with a RuP 2 catalyst could be discharged/charged for more than 200 cycles with an overpotential of lower than 1.3 V, operating at a fixed capacity of 1000 mA h g À 1 .…”
Section: Transition Metals and Their Compoundsmentioning
confidence: 99%
“…[ 108 ] Zou et al designed a 3D dandelion‐like NiCo 2 O 4 catalyst with a hollow nanostructure for Li−CO 2 /O 2 batteries. [ 109 ] Reaction mechanisms of CO 2 /O 2 on this catalyst were systematically investigated. The results revealed that NiCo 2 O 4 nanoparticles could inhibit the aggregation of Li 2 CO 3 and could access the optimal utilization of catalytically active sites (Figure 12b).…”
Section: Cathode Materials and Electrocatalysts For Li–co2 Batteriesmentioning
confidence: 99%
“…Reproduced with permission. [ 109 ] Copyright 2019, Wiley‐VCH. c) Schematic of a Li−CO 2 cell with a ZnCo 2 O 4 @CNT cathode catalyst.…”
Section: Cathode Materials and Electrocatalysts For Li–co2 Batteriesmentioning
confidence: 99%
“…[8][9][10] [11] NiCo 2 O 4 suppresses the growth of Li 2 CO 3 flakes and bares them to clog the active sites. [12] Although the CO 2 reactions are catalyzed by the abovementioned catalysts, the presence of carbon materials, including graphene, carbon nanotube (CNT),a nd carbon black, plays av ital role in their performance as bifunctionalc atalysts. [13,14] The advantages of using carbon-based materials include their electrochemical stability,c onductivity,d iffusion pathways for gas molecules, and high activesurface area.…”
Section: Introductionmentioning
confidence: 99%